Case Report: Acquired Generalized Anhidrosis Caused by Brain Tumor: Review of the Literature - Kawahara, Kohei; Shimomura, Yasuto; Oshima, Yuichiro; Watanabe, Tadashi; Hori, Toshinori; Okumura, Akihisa; Iwayama, Hideyuki (Frontiers in Endocrinology, 2022)
Purpose: There has been limited focus on sweating failure in patients with brain tumor. We report two patients with generalized anhidrosis caused by germinoma. We also review previous reports of generalized anhidrosis due to brain tumor. Case reports: Patient 1 was a 12-year-old boy with repetitive heat shock-like episodes even in winter. Based on Minor’s test, he was diagnosed with generalized anhidrosis. Magnetic resonance imaging (MRI) revealed the absence of high signal intensity of the posterior pituitary. He was initially diagnosed with central diabetes insipidus. However, an MRI scan performed after 3 months revealed an enlarged pituitary stalk. He was finally diagnosed with germinoma by pituitary biopsy. After chemotherapy and radiation, sweating was partially resolved. Patient 2 was a 12-year-old girl with growth hormone deficiency and generalized anhidrosis. She was diagnosed with germinoma based on MRI and pituitary biopsy findings. After chemotherapy and radiation, the sweating resolved completely. Discussion: In our literature search, we identified four patients with anhidrosis due to brain tumor, including our cases. All patients had germinoma and continued to require hormone replacement therapy after treatment of germinoma. Two patients with incomplete recovery of sweating had the involvement in the hypothalamus, whereas one patient with complete recovery showed a lack of evident hypothalamic involvement. Improvement in sweating in one patient was not described. Conclusion: Germinoma can cause anhidrosis, and involvement in the hypothalamus may be relevant to incomplete recovery of sweating.